Startup Characteristics and The Role of Business Incubators in Indonesia - Adhia Ika Wahyuni; Siska Noviaristanti (School of Business, IPB University (SB-IPB), 2022)
One of the positive results of digital transformation in Indonesia is a fairly advanced startup developed and has contributed to Indonesia’s GDP. The issue of success of several Indonesian startups such as Gojek, Traveloka, Tokopedia, and Bukalapak triggered the community to flock to establish a startup, but the startup was established without going through a business incubation program, while business incubators in Indonesia have been around since 1994 long before the startup was founded. This is different from overseas, where startups such as Airbnb and Dropbox, alumni of business incubators, have achieved more than 30 billion USD. This study was conducted to investigate the startup models and the business incubator services that include 992 startups and 23 business incubators in Indonesia. The analysis technique used in this study is a descriptive analysis by identifying websites of 992 startup and 23 business incubators. Sampling was done by the non-probability sampling method with saturation sampling method (census). The data used are startup registered in Indonesia Mapping & Database Startup 2018 and business incubator in Indonesia. The results show that startups with independent model dominate business in Indonesia, with private ownership and from indigenous people. As for services from business incubators in Indonesia, they have provided key services to create sustainability from technopreneurship. Keywords: startup model, startup ownership, startup origin, business incubator, Indonesia